Salman Rushdie’s the satanic verses: the crossroads of locations - Carlos Andrei Assis Siquara (2022)
In this dissertation, I analyze the representation of the urban space in Salman Rushdie’s The Satanic Verses, drawing attention to how the novel appropriates the notion of displacement. For this, I rely on the concept of mobilities, as proposed by John Urry, and its two main manifestations: corporeal and imaginative. Salman Rushdie’s remarks on translation, migration and “imaginative affinities” are recalled in dialogue with such discussion too. I argue that Rushdie’s appropriation might enable the production of a counter-narrative that challenges the notion of place, by dislocating it from a static and homogeneous conception to a dynamic and heterogenous one. Here the writings of Michel De Certeau and Marc Augé, respectively, on the concepts of space and non-place are relevant. I also discuss how the novel suggests a space of travel in which mobility and the shifting of perspectives concerning the city’s imagery is underscored in its relation to the national space. Michel Foucault’s outlining of heterotopia is conjured up to point out how the novel renders fragmented portraits of three main cities: London, Bombay and Jahilia. The starting point is the contrast of the journeys of two characters: Saladin Chamcha and Gibreel Farishta, but other experiences of displacement are considered once they are relevant to investigate the points of view of both characters. Moreover, this research discusses how, by inscribing the routes of diasporas in the imagery of London, The Satanic Verses foster other possibilities of imagining the nation.